New Statistical Simulation Method for Transient Recovery Voltage in the Verification And/Or Selection of Switches in Air Lines with Series Compensation - Travieso-Torres, J; Travieso-Torres, J; Condor-Gaona, C (Institute of Electrical and Electronics Engineers Inc., 2023)
As progress has been made in the implementation of series compensation devices, there is also a need to understand the response of transient recovery voltage generated under different stochastic operating conditions of the switch. The objective is to propose a new non-deterministic methodology based on simulation analysis to obtain the transient recovery voltage and its rate of growth for a high-voltage line with series compensation, aiming to obtain a probability distribution function. This study also includes evaluating the switch s capacity. The response obtained from the studied case utilized the Monte Carlo method as the base structure, with stochastic input variables, along with calculation processing from an EMTP-ATP program. The results obtained through applied statistical techniques yielded a probability density function. The findings from the case study indicate a 22.72% probability that the transient recovery voltage exceeds the phase mismatch peak specified by IEC 62271-100 and IEEE C37.011, suggesting the need for a higher specified capacity. The analysis demonstrated that the probability function, when compared to the switch s peak voltage capability, poses a 22.03% failure risk under the determined conditions in the conducted study. © 2023 IEEE.